2004
DOI: 10.1074/jbc.m401066200
|View full text |Cite
|
Sign up to set email alerts
|

Atg21 Is Required for Effective Recruitment of Atg8 to the Preautophagosomal Structure during the Cvt Pathway

Abstract: Atg21 and Atg18 are homologue yeast proteins. Whereas Atg18 is essential for the Cvt pathway and autophagy, a lack of Atg21 only blocks the Cvt pathway. Our proteinase protection experiments now demonstrate that growing atg21⌬ cells fail to form proaminopeptidase I-containing Cvt vesicles. Quantitative measurement of autophagy in starving atg21⌬ cells showed only 35% of the wild-type rate. This suggests that Atg21 plays a nonessential role in improving the fidelity of autophagy. The intracellular localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 55 publications
9
93
0
Order By: Relevance
“…This suppression also was observed by deleting ATG7 ( Figure 1B) or ATG14 ( Figure 1C), and as expected, the effect was lost after complementation of the deletions with plasmids expressing WT Mcd4, Atg7, and Atg14, respectively. In contrast, deletion of ATG21, a gene required for the selective cytoplasmto-vacuole targeting (Cvt) pathway (Meiling-Wesse et al 2004), was unable to rescue the lethality of mcd4-174 at the restrictive temperature ( Figure 1D). To examine whether the observed phenotype was a general feature of cells with perturbed Mcd4 function, we analyzed whether deletion of ATG7 was able to restore growth of mcd4D or cells harboring the mcd4-P301L allele (Storey et al…”
Section: Identification Of Novel Autophagy Regulators Among the Essenmentioning
confidence: 95%
“…This suppression also was observed by deleting ATG7 ( Figure 1B) or ATG14 ( Figure 1C), and as expected, the effect was lost after complementation of the deletions with plasmids expressing WT Mcd4, Atg7, and Atg14, respectively. In contrast, deletion of ATG21, a gene required for the selective cytoplasmto-vacuole targeting (Cvt) pathway (Meiling-Wesse et al 2004), was unable to rescue the lethality of mcd4-174 at the restrictive temperature ( Figure 1D). To examine whether the observed phenotype was a general feature of cells with perturbed Mcd4 function, we analyzed whether deletion of ATG7 was able to restore growth of mcd4D or cells harboring the mcd4-P301L allele (Storey et al…”
Section: Identification Of Novel Autophagy Regulators Among the Essenmentioning
confidence: 95%
“…However, both Atg18 and Atg21 enable the recruitment of Atg8 (LC3) to the nascent autophagosome (Meiling-Wesse et al, 2004;Nair et al, 2010).…”
Section: Box 2 Atg18 Function In Yeast Autophagymentioning
confidence: 99%
“…Although Atg21 has a function in Atg8 association with the PAS rather than recruiting Atg2 to the same location (Meiling-Wesse et al, 2004;Strømhaug et al, 2004), we examined whether the Atg2-GFP localization observed in our atg18D background was due to Atg21 presence. As shown in Fig.…”
Section: Atg2 Is Recruited To the Pas Independently From Atg18mentioning
confidence: 99%